One-step preparation of alpha-chlorostyrenes - Borate, Hanumant B.; Galkwad, Abaji G.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Kalal, Kamalakar M. (Tetrahedron Letters, 2007)
alpha-Chlorostyrenes were prepared via a one-step method involving Friedel-Crafts reaction of various aromatic substrates with acid chlorides in the presence of a heterogeneous Si-Fe catalyst. (c) 2007 Elsevier Ltd. All rights reserved.

Transesterification of alpha-haloesters and beta-ketoesters over Mg-Al-hydrotalcites (HT)-like anionic clays - Bulbule, Vivek J.; Borate, Hanumant B.; Munot, Yogesh S.; Deshpande, Vishnu H.; Sawargave, Sangmeshwer P.; Gaikwad, Abaji G. (Journal of Molecular Catalysis A-Chemical, 2007)
Transesterification of alpha-haloesters was achieved by reaction of alcohols in the presence of Mg-Al-HT-like anionic clays. beta-Ketoesters were also transesterified under similar conditions on reaction with alcohols with a wide variety of functional groups. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: alpha-haloesters; beta-ketoesters; heterogeneous catalyst; Hydrotalcites; transesterification

Short synthesis of 3,6-disubstituted N-2-thienyl/aryl-indoles - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Maujan, Suleman R. (Tetrahedron Letters, 2009)
A short synthetic strategy for 3,6-disubstituted-N-2-thienyl/aryl-indoles, involving reaction of substituted 2,4-difluoro/dichloro-styrene epoxide with substituted 2-formylaminothiophenes or substitued N-formylanilins in the presence of a base followed by treatment with an acid, has been developed The method was applied for the synthesis of a number of indoles with a variety of substitutents at 1, 3, and 6 positions of the indole moiety. (C) 2009 Elsevier Ltd All rights reserved.
Keywords: Formylaminothiophene; Gewald synthesis; Indole; Styrene epoxide

Fluconazole analogues containing 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moieties, a novel class of anti-Candida agents - Borate, Hanumant B.; Maujan, Suleman R.; Sawargave, Sangmeshwer P.; Chandavarkar, Mohan A.; Vaiude, Sharangi R.; Joshi, Vinay A.; Wakharkar, Radhika D.; Iyer, Ramki; Kelkar, Ramesh G.; Chavan, Subhash P.; Kunte, Sunita S. (Bioorganic & Medicinal Chemistry Letters, 2010)
As a part of our program to develop new antifungal agents, a series of fluconazole analogues was designed and synthesized wherein one of the triazole moieties in fluconazole was replaced with 2H-1,4-benzothiazin-3(4H)-one or 2H-1,4-benzoxazin-3(4H)-one moiety. The new chemical entities thus synthesized were screened against various fungi and it was observed that the compounds 4a and 4i are potent inhibitors of Candida strains. The structure-activity relationship for these compounds is discussed. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: antifungal; Benzothiazinone; Benzoxazinone; Fluconazole

Novel hybrids of fluconazole and furanones: design, synthesis and antifungal activity - Borate, Hanumant B.; Sawargave, Sangmeshwer P.; Chavan, Subhash P.; Chandavarkar, Mohan A.; Iyer, Ramki; Tawte, Amit; Rao, Deepali; Deore, Jaydeep V.; Kudale, Ananada S.; Mahajan, Pankaj S.; Kangire, Gopinath S. (Bioorganic & Medicinal Chemistry Letters, 2011)
During our efforts to develop new antifungal agents, a number of hybrid molecules containing furanones and fluconazole pharmacophores were designed and synthesized. The new chemical entities thus synthesized were tested for their potential as antifungal agents against various fungal strains and it was observed that the compounds with general structure 7 were potent inhibitors of Candida albicans ATCC 24433, Candida glabrata ATCC 90030, Candida tropicalis ATCC 750 and Candida neoformans ATCC 34664 while the fluconazole analogues 12 exhibited antifungal activity against Candida albicans ATCC 24433 and Candida glabrata ATCC 90030. The structure-activity relationship for these compounds is discussed. The synthetic strategies used in the present work have potential to prepare a large number of compounds for further refinement of structures to obtain molecules suitable for development as antifungal drugs. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Antifungal activity; Fluconazole; Furanones

One-step synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines and their use in the synthesis of highly functionalized 2,3,5,6,7-and 2,3,4,5,7-substituted indoles - Sawargave, Sangmeshwer P.; Kudale, Ananada S.; Deore, Jaydeep V.; Bhosale, Dattatry S.; Divse, Jaisingh M.; Chavan, Subhash P.; Borate, Hanumant B. (Tetrahedron Letters, 2011)
A three-component, one-step method for the synthesis of 4-alkyl-3-aryl-2,6-dicyanoanilines involving reaction of alkyl aldehyde, malononitrile and aryl aldehyde in presence of morpholine is reported. Highly functionalized 2,3,5,6,7- and 2,3,4,5,7-substituted indoles were prepared from these dicyanoanilines by reaction with ethyl bromoacetate. These substituted dicyanoanilines and indoles have a potential to be converted into various other compounds taking advantage of various functional groups present in these molecules. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: aldehydes; Dicyanoanilines; indoles; Malononitrile